Description of female of Titidius urucu Esmerio & Lise, 1996 (Araneae: Thomisidae) - Amanda, Naila; Salvatierra, Lidianne; Almeida, Marlus Queiroz; de Morais, José Wellington (Zootaxa, 2018)
The genus Titidius Simon, 1895 belongs to the family Thomisidae Sundevall, 1833 and can be easily identified from the related genera Tmarus Simon, 1875 and Acentroscelus Simon, 1886 by the high carapace, anterior eye row straight and posterior eye row recurve-;pd in dorsal view, carapace smooth with moderate setation, abdomen longer than wide, legs long, slender and setose and clypeus vertical (Esmerio & Lise 1996). It is currently composed of 20 species, all occurring in Brazil with exception of Titidius ignestii Caporiacco, 1947 from Guyana (World Spider Catalog 2017). Eight species are distributed in the Amazon region (Esmerio & Lise 1996): T. caninde Esmerio & Lise, 1996, T. gurupi Esmerio & Lise, 1996, T. multifasciatus Mello-Leitão, 1929 and T. rubrosignatus (Keyserling, 1880) from Pará; T. galbanatus (Keyserling, 1880) from Amazonas and Pará; T. quinquenatus Mello-Leitão, 1929 and T. urucu from Amazonas; and T. rubescens Carporiacco, 1947 from Amazonas and Roraima.